Expectations of breast-conserving therapy: a qualitative study - Sarah Fuzesi; Karima Becetti; Anne F. Klassen; Mary L. Gemignani; Andrea L. Pusic (SpringerOpen, 2019)
Abstract Background Early-stage breast cancer is often treated with breast-conserving therapy (BCT), including lumpectomy with radiation therapy. Patients' expectations of BCT remain largely unknown. Expectations affect perceptions of treatment-related experiences and health-related quality of life (HR-QOL) outcomes. Our primary aim was to describe expectations of BCT among patients with early breast cancer through qualitative methods. Our secondary aim was to inform preoperative patient education and improve the patient experience through knowledge. Methods We used a grounded-theory approach to investigate a convenience sample of 22 women with stage I and II breast cancer who were treated with BCT at a single hospital in New York City between May and August 2016. Semi-structured interviews were conducted in person and by telephone. Open-ended questions covered participants' expectations of treatment experiences and outcomes. Data was analyzed in a line-by-line approach to identify emergent themes related to patient expectations. Interviews continued until no new themes emerged. Results Analysis of data identified the following themes related to patient expectations of BCT: experience of cancer care, recovery, appearance, and HR-QOL. Despite preoperative informed consent and teaching, participants expressed few expectations preoperatively, owing to a lack of knowledge about the process of care. Lack of expectations preoperatively was compensated with available care and resources postoperatively. Conclusions Patients in our sample had a surprisingly limited understanding of what to expect during treatment with BCT. Despite available information and preoperative teaching, patients have a clear knowledge gap regarding BCT. These findings suggest patients often undergo cancer treatment with trust rather than complete understanding of the process. This data may be used to enhance preoperative discussions aimed at preparing patients for surgery and treatment.